ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI BERWIRAUSAHA PADA MAHASISWA S1 FEB UNUD - Adi Kusuma, Wirananda; Warmika, Ketut (E-Jurnal Manajemen, 2016)
Indonesia face economic growth problem to embrace 2015 ASEAN economic people, therefore, the government starts to empower entrepreneurial intention by taking entrepreneurial education into the lecture. The purpose of this stud was to find the effect significances of entrepreneurial motivation, needs of achievement and entrepreneurial education on entrepreneurial intention. This research was conducted in faculty of economics of udayana university and took 119 samples of their student using purposive sampling method. Muti linear regression analysis was used to measure this study. The hypothesis test showed that entrepreneurial motivation, needs of achievement and entrepreneurial education has positive and significant effect on entrepreneurial intention. According to the study result, individual who about to be an entrepreneur should concentrate on the effect of  entrepreneurial motivation, needs of achievement and entrepreneurial education as a consideration on implying entrepreneurial intention because these variables has positive and significant effect on entrepreneurial intention.
Keywords: Entrepreneurship motivation, needs of achievement, entrepreneurial eduction, entrepreneurial intention